Effectiveness of Digital Health Interventions in Optimizing Parental Support For Adolescent Type 1 Diabetes Mellitus Management: A Systematic Review - Elvi Kurnia Damayanti; Andri Setiya Wahyudi; Praba Diyan Rachmawati (Universitas Pahlawan Tuanku Tambusai, 2026)
Adolescents with Type 1 Diabetes Mellitus (T1DM) require consistent self-management support, where parental involvement is crucial. However, the complexity of diabetes care often places a significant burden on families. Digital health interventions (DHIs) offer innovative ways to strengthen parental support but require further evaluation. This systematic review aims to examine the effectiveness of DHIs in optimizing parental support for adolescents managing T1DM. A systematic search was conducted across Scopus, PubMed, Web of Science, and ProQuest for studies published from 2015 to 2025. Following PRISMA guidelines, randomized controlled trials involving DHIs for parents of adolescents with T1DM were included. Quality was appraised using the Joanna Briggs Institute (JBI) checklist.Eleven studies were included, featuring DHIs such as mobile apps, web-based education, telehealth, and remote monitoring. These interventions improved parental outcomes, including increased knowledge, reduced stress, better monitoring, and greater self-efficacy. Adolescents also showed improved glycemic control, adherence, and emotional well-being.DHIs are effective in strengthening parental support and engagement in adolescent diabetes care. Integrating DHIs into family-centered nursing practice may enhance chronic illness management. Future studies should address cultural adaptations and long-term impacts.